Air source thermoelectric heat pump for simultaneous cold air delivery and hot water supply: Full modeling and performance evaluation. (January 2019) - Cai, Yang; Zhang, Dong-Dong; Liu, Di; Zhao, Fu-Yun; Wang, Han-Qing
Abstract: An air-source thermoelectric heat pump (AS-THP) system is proposed in the present work, and it actively exploits ambient air source energy serving for cold air delivery and hot water supply simultaneously. A mathematical model, combining thermoelectric theory and the effectiveness-number of transfer units ( ε-NTU ), is firstly conducted to predict the performance of AS-THP system. Subsequently, the effects of thermoelectric input current, inlet air/water temperatures, thermal conductance, mass flow rate in both cold and hot sides, and the number of thermoelectric coolers on the performance of AS-THP system are sensitively investigated. Modeling results demonstrate that the thermal conductance and specific heat allocations in heat exchanger hot and cold sides could put heavy effects on the total cooling capacity ( Q c, all ), coefficient of performance ( COP), outlet water temperature ( T c, out ) and outlet air temperature ( T h, out ). Further modeling on the thermal parameters in both sides has shown that overall efficiency of AS-THP system could be achieved to nearly 90%. Also, with the increase of unit number, the cooling load for each thermoelectric unit would be reduced while the input power increases inversely. Present research could be beneficial for extensive utilization of thermoelectric heat pump in daily life by the use of ambient air source energy. Highlights: Air source driven thermoelectric heat pump aims to supplies of cold air and hot water. Hybrid methodology is proposed to model the full performance of AS-THP system. An exhaustive evaluation intends to fully optimize the performance of AS-THP system. Multiple governing parameters and factors are confirmed by the optimal design. AS-THP system could be applied due to its miniature, feasibility and flexibility.